“Shining a LAMP” (Loop-Mediated Isothermal Amplification) on the Molecular Detection of Phytopathogens Phytophthora spp. and Phytophthora cactorum in Strawberry Fields - Dominika G. Siegieda (MDPI AG, 2021)
Phytopathogenic microorganisms belonging to the genus Phytophthora have been recognized many times as causal agents of diseases that lower the yield of many plants important for agriculture. Meanwhile, Phytophthora cactorum causes crown rot and leather rot of berry fruits, mainly strawberries. However, widely-applied culture-based methods used for the detection of pathogens are time-consuming and often inaccurate. What is more, molecular techniques require costly equipment. Here we show a rapid and effective detection method for the aforementioned targets, deploying a simple molecular biology technique, Loop-Mediated Isothermal Amplification (LAMP). We optimized assays to amplify the translation elongation factor 1-α (EF1a) gene for two targets: Phytophthora spp. And Phytophthora cactorum. We optimized the LAMP on pure strains of the pathogens, isolated from organic plantations of strawberry, and successfully validated the assay on biological material from the environment including soil samples, rhizosphere, shoots and roots of strawberry, and with SYBR Green. Our results demonstrate that a simple and reliable molecular detection method, that requires only a thermoblock and simple DNA isolation kit, can be successfully applied to detect pathogens that are difficult to separate from the field. We anticipate our findings to be a starting point for developing easier and faster modifications of the isothermal detection methods and which can be applied directly in the plantation, in particular with the use of freeze-dried reagents and chemistry, allowing observation of the results with the naked eye.